Modification of a modulated arc total body irradiation technique: Implementation and first clinical experience for paediatric patients. Issue 4 (19th September 2018) - Pemberton, Melanie; Brady, Carole; Taylor, Beth; Tyrrell, Danielle; Sim, Lucy; Zawlodzka‐Bednarz, Sylwia; Biggs, Jennifer; Peters, Mitchell; Baines, John; Hargrave, Catriona
Abstract: Introduction: To implement the modulated arc total body irradiation (MATBI) technique within the existing infrastructure of a radiation oncology department. The technique needed to treat paediatric patients of all ages, some of whom would require general anaesthesia (GA). Methods: The MATBI technique required minor modifications to be incorporated within existing departmental infrastructure. Ancillary equipment essential to the technique were identified and in some cases custom designed to meet health and safety criteria. GA equipment was also considered. To evaluate the effectiveness of the implemented technique, an audit of the cases clinically treated was conducted. Results: A motorised treatment couch was designed to allow the patient to be positioned in stabilisation equipment at a height, then lowered to the floor to accommodate source‐to‐skin‐distances from 180 cm to 198 cm to treat the fixed 40 cm × 40 cm field size. Treatment couch design also facilitated positioning of the bespoke two‐part spoiler. While organ at risk dose is limited using a beam weight optimisation technique, the dose is further reduced using compensators placed close to the patient's skin on a 3D printed custom‐made support bridge. A digital radiography system is used to verify compensator position. Fifteen patients have been treated to date for various diseases using a variety of dose fractionations ranging from 2 Gy in a single fraction to 12 Gy in 6 fractions. Five patients have required GA due to age or behavioural issues. Conclusion: The modified MATBI technique and the equipment required for treatment delivery has been found to be well tolerated by all patients. Abstract : Implementation and modification of the modulated arc total body irradiation technique within an established department. Paediatric patients of all ages need to be accommodated within the technique on custom made equipment.